2018
DOI: 10.1097/gox.0000000000002049
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Utilization of the Digital Atasoy Flap

Abstract: Background:The Atasoy, or Kleinert flap, is well-known to hand surgeons. This triangular volar V-Y flap is frequently used for reconstruction of fingertip amputations with exposed bone. It is indicated in transverse amputations or in dorsal oblique amputations, providing replacement of an area of skin and subcutaneous tissues with sensibility. Originally, this flap was not recommended for use in volar oblique amputations (greater volar tissue loss). With the described modifications and recommendations, modest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…4 ). Viciana and Lessard et al 18 reported that AF reconstructions can be used to cover modest volar oblique amputations in a single stage. However, long-term outcomes of AF reconstructions for volar oblique injuries are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Viciana and Lessard et al 18 reported that AF reconstructions can be used to cover modest volar oblique amputations in a single stage. However, long-term outcomes of AF reconstructions for volar oblique injuries are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes mellitus with vascular involvement, consideration should be given to a surgical delay of the flap by incising through skin only and completion of the flap at 14 days. 12 When closing areas with exposed vital tissues or exposed bone, or areas at risk for contamination such as pilonidal disease, fasciocutaneous flaps are more robust and, therefore, more protective than cutaneous flaps.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…In patients with diabetes mellitus with vascular involvement, consideration should be given to a surgical delay of the flap by incising through skin only and completion of the flap at 14 days. 12 …”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Patients with potential for poor wound healing include those with diabetes mellitus, Raynaud’s disease, severe peripheral vascular disease, or connective tissue diseases, such as scleroderma, systematic lupus erythythematosus (SLE), dermatomyositis, and calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia (CREST) syndrome. 14 The complete clinical picture, however, should be considered. If the patient is not infirm and their underlying disease is well-controlled, then a flap repair is indicated.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%